2020
DOI: 10.3168/jds.2019-17169
|View full text |Cite
|
Sign up to set email alerts
|

Liquid molasses interacts with buffers to affect ruminal fermentation, milk fatty acid profile, and milk fat synthesis in dairy cows fed high-concentrate diets

Abstract: We aimed to evaluate the effects of feeding sugarcane liquid molasses (LM) with or without a commercial buffer mix (BFM) on ruminal fermentation parameters, milk fatty acid (FA) profile, and milk yield and composition in dairy cows fed high-concentrate diets (35:65 forage-to-concentrate ratio). Eight multiparous Holstein cows (4 ruminally cannulated) averaging 165 ± 12 d in milk at the beginning of the study were randomly assigned to a replicated 4 × 4 Latin square design with a 2 × 2 factorial arrangement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
8
1
Order By: Relevance
“…The average ruminal pH of cows in the present study was 6.30. This value is high and inconsistent with previous studies where high-concentrate diets were tested (Voelker and Allen, 2003b;Kahyani et al, 2019;Nasrollahi et al, 2019;Razzaghi et al, 2020). Two main differences between the present study and these referenced reports were different sorting activities of cows and supplementation of sodium bicarbonate.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The average ruminal pH of cows in the present study was 6.30. This value is high and inconsistent with previous studies where high-concentrate diets were tested (Voelker and Allen, 2003b;Kahyani et al, 2019;Nasrollahi et al, 2019;Razzaghi et al, 2020). Two main differences between the present study and these referenced reports were different sorting activities of cows and supplementation of sodium bicarbonate.…”
Section: Discussioncontrasting
confidence: 99%
“…The effect of ingestion of long particles on increased ruminal pH may be related to increased chewing activity and improved ruminal health and function (Mertens, 1997). Using sodium bicarbonate in the present study also could have contributed to the higher ruminal pH that was observed, compared with previous studies that did not use sodium bicarbonate (Voelker and Allen, 2003b;Nasrollahi et al, 2019;Razzaghi et al, 2020).…”
Section: Discussionmentioning
confidence: 55%
“…In fact, the addition of 0.4% magnesium oxide and 0.8% calciummagnesium dolomite to the diet did not affect feed in-take in our study. Other studies in lactating dairy cows showed that buffering or alkalizing agents had no effect on lactation performance, either in typical (Cabrita et al, 2009;Rauch et al, 2012) or high-concentrate diets (Kalscheur et al, 1997;Khorasani and Kennelly, 2001); however, other studies (Neville et al, 2019;Razzaghi et al, 2020) reported increased feed intake. Rauch et al (2012) reported that there was no difference in feed intake and milk yield between control and calciummagnesium dolomite diets on commercial dairy farms, but differences in dietary starch and NDF contents compared with our study were evident (starch = 15.7 vs. 35.2% and NDF = 33.9 vs. 28.7%, on DM basis).…”
Section: Diets Performance and Milk Fat Synthesismentioning
confidence: 95%
“…In addition, there are divergent results regarding the effects of feeding buffers on milk yield. Some studies have documented no effects (Bach et al, 2018;Razzaghi et al, 2020), whereas others have reported increased milk yield (Razzaghi et al, 2021) with the addition of buffering or alkalizing agents.…”
Section: Diets Performance and Milk Fat Synthesismentioning
confidence: 99%
See 1 more Smart Citation